2019
DOI: 10.1007/s10856-019-6288-9
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic potential of sol–gel bioactive glasses containing manganese

Abstract: We report that the release of manganese ions from bioactive glass provoked human mesenchymal stem cell (hMSC) differentiation down a bone pathway, whereas hMSCs exposed to the Mn-free glass did not differentiate. Bioactive glasses (BGs) are widely used for bone regeneration, and allow the incorporation of different ions with therapeutic properties into the glass network. Amongst the different ions with therapeutic benefits, manganese (Mn) has been shown to influence bone metabolism and activate human osteoblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 69 publications
3
33
0
Order By: Relevance
“…In this context, Mn ions have been shown to upregulate osteogenic marker genes and to improve extracellular matrix (ECM) formation when added to cell culture settings 7,13‐17 . There are several other ions with distinct therapeutic activity, which are interesting for application in BTE such as zinc (Zn) and copper (Cu) 8,18 .…”
Section: Introductionmentioning
confidence: 99%
“…In this context, Mn ions have been shown to upregulate osteogenic marker genes and to improve extracellular matrix (ECM) formation when added to cell culture settings 7,13‐17 . There are several other ions with distinct therapeutic activity, which are interesting for application in BTE such as zinc (Zn) and copper (Cu) 8,18 .…”
Section: Introductionmentioning
confidence: 99%
“…12 That Mn can stimulate the growth of osteoblasts and bone regeneration has also emerged from in vitro studies on bioactive glass, in which it has been observed how the addition of Mn is able to promote, in cultures of human osteoblasts, the expression of alkaline phosphatase (ALP) and some bone morphogenetic proteins (BMPs), 13 and to stimulate the osteogenetic differentiation of human mesenchymal stem cells (hMSCs) and influence the mineralization process by increasing the expression of markers of osteogenetic differentiation, such as type I collagen, osteopontin and osteocalcin. 14…”
Section: Studies On Animal and In Vitro Modelsmentioning
confidence: 99%
“…Manganese (Mn) is one of the most abundant transition metals in the earth's crust and is an essential trace element of the human body. Mn is involved in regulating metabolism of macromolecules (carbohydrates, lipids, and proteins), immune response, bone formation, free radical scavenging, and reproduction (Barrioni et al, 2019; Kehl‐Fie & Skaar, 2010; Lee et al, 2006; Li & Yang, 2018). This trace element also acts as an activator and cofactor of many enzymes, including transferases, hydrolases, and oxidoreductases (Crowley et al, 2000).…”
Section: Introductionmentioning
confidence: 99%